Ru-based catalyst doped with rare earth element as well as preparation method and application of Ru-based catalyst
By doping the Ru-based catalyst on the nitrogen-doped mesoporous carbon support, the problem of Ru-based catalysts in the alkaline HER reaction is solved, and efficient catalysis under the ampere-level current density is achieved Performance and long-term stability, suitable for AEM electrolytics applications.
Patent Information
- Application Number
- CN202411172713.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-27
AI Technical Summary
The existing Ru-based catalysts have problems of active site poisoning and poor stability in basic HER reactions, especially at ampere-level current density, which is poor in catalytic activity and stability, which cannot meet the practical application needs of AEM electrolytic cells.
The RuxREy-NMC catalyst is prepared by loading Ru metal ions and rare earth metal ions onto a nitrogen-doped mesoporous polymer using the strong oxygen affinity of rare earth elements. , and the catalytic activity is improved by doping the mesoporous carbon material as a support.
It has achieved the improvement of catalytic activity and stability under the current density of ampere level, has excellent HER performance, is low cost, is suitable for large-scale preparation and industrial applications, and the assembled electrolytic cell structure is simple and easy to operate.
Smart Images

Figure CN119194496A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical energy materials, and in particular relates to a rare earth element doped Ru-based catalyst and a preparation method and application thereof. Background Art
[0002] In order to alleviate the excessive dependence of social development on fossil fuels and to cope with the challenge of global warming, clean and renewable energy has become a research hotspot. Hydrogen energy is regarded as an ideal energy carrier due to its advantages such as high energy density and zero carbon emissions. Among all hydrogen production methods, anion exchange membrane (AEM) water electrolysis technology has excellent dynamic response, high hydrogen production purity, mild reaction conditions, low cost, and broad application prospects. As the cathode reaction in the AEM electrolyzer, the electrocatalytic hydrogen evolution reaction (HER) has slow reaction kinetics and has long relied on Pt-based catalysts, but its low abundance and high price limit the large-scale application of AEM electrolyzers. Therefore, the development of precious metal catalysts with high-quality activity to accelerate the HER reaction kinetics and reduce the reaction energy barrier is one of the most urgent needs in AEM water electrolysis hydrogen production technology.
[0003] Among the platinum (Pt) family of noble metals, ruthenium (Ru) has the lowest price, has a similar metal-hydrogen bond (MH) strength to Pt, and has a stronger water dissociation ability, making it an ideal choice to replace Pt to catalyze HER reactions. In the field of alkaline HER research, the core requirement for electrocatalysts is not only to have efficient H2O dissociation ability, but also to have appropriate H* adsorption energy. In contrast, less attention has been paid to the effect of the adsorption capacity of the reaction intermediate hydroxyl (OH*) at the active site on the reaction. However, excessive adsorption of OH* at the Ru site will cause poisoning of the active site, affect the occurrence of subsequent reactions, and is not conducive to the rapid and sustainable progress of alkaline HER. In recent years, Feng et al. (Angew. Chem. Int. Ed. 2022, 61, e202209486.) first introduced the oxygen-philic component tin oxide (SnO2) into Ru-based catalysts, and alleviated the poisoning effect of OH* on Ru sites through the competitive adsorption of SnO2 on OH*, effectively promoting the regeneration of Ru active sites and achieving excellent HER activity. Therefore, introducing heterogeneous elements to regulate the OH adsorption environment of Ru is an effective strategy to enhance the HER reaction kinetics, especially at ampere-level current densities. Rare earth metals (RE) have strong oxophilicity, and it is theoretically feasible to dope them in Ru-based catalysts to alleviate the poisoning effect of active sites. Zhou et al. combined cerium (Ce) single atoms and Ru nanoclusters on nitrogen-modified carbon supports, and took advantage of the strong oxophilicity of Ce to make OH* generated by water dissociation selectively bind to Ce single atoms, while H* is moderately adsorbed on Ru nanoclusters, thereby achieving excellent HER performance. However, the design of this catalyst still has the following challenges: (1) Metal particles will migrate and agglomerate during the catalyst preparation process, resulting in the loss of active sites. Usually, a suitable carrier is required to anchor Ru nanoparticles and single atom sites; (2) Rare earth catalysts still have some synthesis barriers and intrinsic defects. For example, their large atomic radius leads to a tendency to migrate to the catalyst surface during high-temperature treatment, resulting in a reduction in the number of active sites. At the same time, rare earth elements themselves have almost no catalytic activity as co-catalysts. (3) Catalysts can usually achieve excellent HER performance at lower current densities, but their catalytic activity and stability at ampere-level current densities are poor, which cannot meet the practical application in AEM electrolyzers. To solve the above problems, a simple and easy-to-operate synthesis method is needed to prepare efficient and stable HER electrocatalysts. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a rare earth element doped Ru-based catalyst and its preparation method and application. The preparation method is simple to operate, optimizes the adsorption capacity of the catalyst active sites for reaction intermediates, improves the intrinsic activity of the catalyst, and can be applied to the cathode of an AEM electrolytic cell, solving the problem of poor catalytic activity at ampere-level current density.
[0005] The technical solutions adopted are:
[0006] A rare earth element doped Ru-based catalyst, the molecular formula is Ru x RE y -NMC, Ru metal ions and rare earth metal ions are loaded on nitrogen-doped mesoporous polymers; wherein x=0.5-3, y=0.01-0.1, and RE is any one of neodymium, cerium, lanthanum, samarium, gadolinium, erbium, dysprosium, yttrium, and praseodymium.
[0007] A method for preparing a rare earth element-doped Ru-based catalyst comprises the following steps:
[0008] (1) Place the template F127 in a beaker, add deionized water, fully dissolve it, then add methyltetramine, and stir evenly to prepare solution A;
[0009] At the same time, add deionized water to another beaker, then add the phenolic compound, and stir thoroughly to prepare solution B;
[0010] Then, solution A and solution B are mixed and stirred evenly, and then placed in a polytetrafluoroethylene reactor for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled to room temperature in an oven. The reaction product is centrifuged several times with deionized water and then freeze-dried to obtain a nitrogen-doped mesoporous polymer NMP.
[0011] (2) dissolving the nitrogen-doped mesoporous polymer NMP in deionized water, ultrasonicating and stirring to obtain a solution C;
[0012] Subsequently, the ruthenium trichloride aqueous solution and the rare earth metal salt solution were added dropwise to the solution C to obtain a mixed solution D, which was stirred until uniform and then freeze-dried to obtain a nitrogen-doped mesoporous polymer loaded with metal precursor Ru x RE y -NMP;
[0013] (3) x RE y -NMP was fully ground, and then carbonized at 600-900°C in an Ar atmosphere, kept warm, and then naturally cooled to room temperature to obtain a rare earth element-doped Ru-based catalyst Ru x RE y -NMC.
[0014] Preferably, in the step (1), methyltetramine is added in 4 to 6 portions; the phenolic compound is a mixture of one or more of 2-aminophenol, 3-aminophenol and 4-aminophenol;
[0015] The mass ratio of template F127 to phenolic compound is 0.3-0.7:1;
[0016] The mass ratio of the phenolic compound to the total amount of methyltetramine added to solution A is 1-2:1.
[0017] Preferably, in step (1), the hydrothermal reaction conditions are: heating to 80-100°C at a heating rate of 2°C / min, and then keeping warm for 20-24 hours; the freeze-drying conditions are -40--60°C, and the vacuum degree is 5-20 kPa. In the preparation method of the present invention, the freeze-drying conditions of other steps are also -40--60°C, and the vacuum degree is 5-20 kPa.
[0018] Preferably, in the step (2), after being dissolved in deionized water, the concentration range of the nitrogen-doped mesoporous polymer NMP aqueous solution is 2 to 7 mg / mL; the rare earth metal salt solution is any one of a neodymium trichloride hexahydrate aqueous solution, a cerium trichloride heptahydrate aqueous solution, a lanthanum trichloride heptahydrate aqueous solution, a samarium nitrate hexahydrate aqueous solution, a gadolinium nitrate hexahydrate aqueous solution, an erbium nitrate hexahydrate aqueous solution, a dysprosium nitrate hexahydrate aqueous solution, a yttrium nitrate hexahydrate aqueous solution, and a praseodymium nitrate hexahydrate aqueous solution.
[0019] Preferably, in the step (3), in the catalyst prepared, the loading amount of Ru is 0.5-10 wt%, and the loading amount of RE is 0.01-0.4 wt%.
[0020] Preferably, in the catalyst prepared in step (3), the metal Ru exists in the form of nanoparticles and single atoms with an average diameter in the range of 3 to 6 nm, and the rare earth metal exists only in the form of single atoms, forming a structure of Ru nanoparticles and Ru and RE double single atoms.
[0021] A rare earth element doped Ru-based catalyst is used for the cathode of an AEM electrolyzer in the electrolysis of water to produce hydrogen. An anion exchange membrane electrolyzer is assembled, which includes a cathode catalyst layer, an anode catalyst layer, a gas diffusion layer, an anion exchange membrane and two end plates. The device uses an electrochemical workstation to electrolyze water in a 1.0M KOH electrolyte.
[0022] Preferably, the catalyst is dispersed in a Nafion mixed solution to obtain a catalyst dispersion, which is then evenly drop-coated onto the electrode surface.
[0023] Preferably, the Nafion mixed solution includes water, isopropanol and Nafion, and the volume ratio of the three is 4:1:0.1-0.2;
[0024] The catalyst concentration in the dispersion is 10-15 mg / mL; the Ru loading is 40-100 μg / cm 2 .
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention uses nitrogen-doped mesoporous carbon materials as carriers to accelerate the kinetics of hydrogen evolution reaction. At the same time, the hierarchical porous structure and large specific surface area and transmission channels are conducive to the full exposure of active sites and the rapid transmission of protons and electrons. At the same time, the nitrogen element on the carrier becomes an anchor point for the metal, preventing the migration and agglomeration of particles, improving the atomic utilization of Ru, and improving its catalytic activity.
[0027] (2) The present invention uses rare earth elements as heterogeneous elements to regulate the hydrogen evolution performance of Ru-based catalysts. On the one hand, the unique 4f unsaturated electron orbital of rare earth elements is more flexible and special in regulating the electronic structure of the catalyst. Specifically, the coupling between the d orbital of Ru and the f orbital of rare earth elements can establish a df electronic ladder, which is beneficial to charge transfer and optimizes the adsorption energy of reaction intermediates; on the other hand, the strong oxygen affinity of rare earth elements themselves can further regulate the adsorption and desorption behavior of OH* during the alkaline hydrogen evolution reaction.
[0028] (3) The synthesis method provided by the present invention is simple to operate and low in cost. The synthesized rare earth element-doped Ru-based electrocatalyst exhibits alkaline HER performance comparable to that of commercial Pt / C catalysts and has certain commercialization potential.
[0029] (4) The rare earth element-doped Ru-based catalyst provided by the present invention has a lower precious metal loading, which reduces the production cost and is expected to be prepared in large quantities. It can also be used as an electrode catalytic material in an alkaline water electrolysis hydrogen production device.
[0030] (5) The rare earth element doped Ru-based electrocatalyst provided by the present invention not only has excellent HER performance at a small current density in an alkaline environment, but also has excellent ampere-level current density catalytic hydrogen evolution performance, and can achieve stable operation for a long time. It can be used as a cathode catalyst for an AEM electrolyzer and has certain industrial application prospects.
[0031] (6) The alkaline anion exchange membrane electrolyzer assembled by the present invention has the advantages of simple structure, easy and understandable assembly, good sealing effect, and is not prone to leakage and short circuit. The device can work under alkaline, pure water, pure seawater, alkaline seawater and other conditions. Through the cathode catalyst provided by the present invention, a good catalytic performance of the AEM electrolyzer is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a high-resolution transmission electron microscopy (HRTEM) image of a Ru-based catalyst doped with a single atom of rare earth metal Nd.
[0033] Figure 2 AC HAADF-STEM image of rare earth metal Nd single atom doped Ru-based catalyst.
[0034] Figure 3 XRD images of nitrogen-doped mesoporous carbon-supported Ru-based catalyst and rare earth metal Nd single atom-doped Ru-based catalyst.
[0035] Figure 4 Figure 2 shows the N2 adsorption / desorption curves and pore size distribution of nitrogen-doped mesoporous carbon-supported Ru-based catalysts and rare earth metal Nd single-atom doped Ru-based catalysts. 0.05 N2 adsorption-desorption curves of -NMC, (b) Ru1Nd 0.05 -NMC, (c) is the N2 adsorption-desorption curve of Ru1-NMC, and (d) is the pore size distribution of Ru1-NMC.
[0036] Figure 5 LSV curves of nitrogen-doped mesoporous carbon-supported Ru-based catalyst, rare earth metal Nd single atom-doped Ru-based catalyst and commercial Pt / C catalyst in alkaline environment (1M KOH).
[0037] Figure 6 Mass activity diagram of nitrogen-doped mesoporous carbon-supported Ru-based catalyst, rare earth metal Nd single atom-doped Ru-based catalyst and commercial Pt / C catalyst at -0.15 V vs. RHE.
[0038] Figure 7 LSV curves of rare earth metal Nd single atom doped Ru-based catalyst used in the cathode of AEM electrolyzer at different temperatures (1M KOH). DETAILED DESCRIPTION
[0039] The accompanying drawings are only used for exemplary description; the present invention will be further described in detail below in conjunction with specific embodiments, but is not limited to the embodiments.
[0040] Example 1. Preparation of Nitrogen-doped Mesoporous Carbon Supported Ru-based Catalyst (Ru1-NMC)
[0041] In order to compare the performance difference between Ru-based catalysts without rare earth element doping and Ru-based catalysts doped with rare earth metal single atoms, a nitrogen-doped mesoporous carbon-supported Ru-based catalyst material was first prepared.
[0042] The specific preparation method comprises the following steps:
[0043] (1) 0.16 g of F127 was placed in a beaker, 30 mL of deionized water was added, and the mixture was fully dissolved. Then, 0.28 g of hexamethylenetetramine was added and stirred to obtain solution A. At the same time, 0.36 g of 3-aminophenol was added to 50 mL of deionized water and stirred to obtain solution B. Then, solution A and solution B were mixed and stirred to obtain solution B. The mixture was placed in a polytetrafluoroethylene reactor for hydrothermal reaction and kept at 80° C. for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature in an oven. The reaction product was centrifuged several times with deionized water and then freeze-dried to obtain the product nitrogen-doped mesoporous polymer NMP.
[0044] (2) 100 mg of nitrogen-doped mesoporous polymer NMP was dissolved in 28 mL of deionized water, and the mixture was ultrasonicated for 30 min and then stirred for 30 min to obtain solution C; then 1 mL of 5.32 mg / mL RuCl3 solution was added dropwise to solution C, and the mixture was stirred for 5 min after the addition was completed. After the addition was completed, the obtained mixed solution D was freeze-dried for 72 h to obtain nitrogen-doped mesoporous polymer-loaded metal Ru precursor Ru1-NMP;
[0045] (3) Take an appropriate amount of nitrogen-doped mesoporous polymer-loaded metal Ru precursor Ru1-NMP and put it into a tubular furnace. Heat it to 700°C at a heating rate of 2°C / min, and calcine it at high temperature in an Ar atmosphere. After keeping it warm for 180 minutes, cool it naturally to room temperature to obtain a nitrogen-doped mesoporous carbon-loaded Ru-based catalyst Ru1-NMC.
[0046] Example 2: Rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.05 Preparation of -NMC:
[0047] (1) 0.16 g of F127 was placed in a beaker, 30 mL of deionized water was added, and the mixture was fully dissolved. Then, 0.28 g of hexamethylenetetramine was added and stirred to obtain solution A. At the same time, 0.36 g of 3-aminophenol was added to 50 mL of deionized water and stirred to obtain solution B. Then, solution A and solution B were mixed and stirred to obtain solution B. The mixture was placed in a polytetrafluoroethylene reactor for hydrothermal reaction and kept at 80° C. for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature in an oven. The reaction product was centrifuged several times with deionized water and then freeze-dried to obtain the product nitrogen-doped mesoporous polymer NMP.
[0048] (2) 100 mg of nitrogen-doped mesoporous polymer NMP was dissolved in 28 mL of deionized water, and the mixture was ultrasonicated for 30 min and then stirred for 30 min to obtain solution C. Subsequently, 0.5 mL of 0.92 mg / mL NdCl3·6H2O solution was added dropwise to solution C and stirred for 5 min. Then, 1 mL of 5.32 mg / mL RuCl3 solution was added dropwise to solution C. After the addition was completed, the mixture was stirred for 5 min. After the addition was completed, the mixture was freeze-dried for 72 h to obtain the nitrogen-doped mesoporous polymer loaded metal RuNd precursor Ru1Nd 0.05 -NMP;
[0049] (3) Take an appropriate amount of nitrogen-doped mesoporous polymer to load the metal RuNd precursor Ru1Nd 0.05 -NMP was placed in a tube furnace and heated to 700°C at a heating rate of 2°C / min. It was calcined at high temperature in an Ar atmosphere and naturally cooled to room temperature after being kept at this temperature for 180 min to obtain a rare earth metal Nd single atom doped Ru-based catalyst Ru1Nd 0.05 -NMC.
[0050] from Figure 1 High-resolution transmission electron microscopy (HRTEM) images show that the rare earth metal Nd single atom doped Ru-based catalyst Ru1Nd 0.05 The presence of mesoporous structure can be observed on the carbon support of -NMC, and the average particle size of Ru nanoparticles distributed on the carbon support is 4.35nm. AC HAADF-STEM image ( Figure 2 ) shows the presence of nanoparticles and single atoms.
[0051] From the XRD pattern ( Figure 3 ) It can be seen that Ru1Nd 0.05 -NMC and Ru1-NMC have a carbon (002) crystal plane diffraction peak at 23.4°. At the same time, there are diffraction peaks of metallic Ru at 38.3°, 42.0°, and 44.0°, indicating that Ru is loaded on the nitrogen-doped mesoporous carbon support in the form of nanoparticles.
[0052] R 0.05 -NMC and Ru1-NMC N2 adsorption-desorption isotherms show typical IV type curves ( Figure 4 ), indicating that the catalyst contains a large number of mesoporous structures. The pore size distribution results show that the mesopore size is mainly concentrated in the range of 2-4nm. Ru1Nd 0.05 -The specific surface area of NMC is 732.9m 2 g -1 , higher than 545.3m of Ru1-NMC 2 g -1 .
[0053] Example 3: Rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.01 Preparation of -NMC:
[0054] The sample was prepared by the same method as in Example 2, except that the 0.92 mg / mL NdCl3·6H2O solution in step (c) was replaced with a 0.184 mg / mL NdCl3·6H2O solution.
[0055] Example 4: Rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.025 Preparation of -NMC:
[0056] The sample was prepared by the same method as in Example 2, except that the 0.92 mg / mL NdCl3·6H2O solution in step (c) was replaced with a 0.46 mg / mL NdCl3·6H2O solution.
[0057] Example 5: Rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.075 Preparation of -NMC:
[0058] The sample was prepared in the same manner as in Example 2, except that the 0.92 mg / mL NdCl3·6H2O solution in step (c) was replaced with a 1.38 mg / mL NdCl3·6H2O solution.
[0059] Example 6: Rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.1 Preparation of -NMC:
[0060] The sample was prepared by the same method as in Example 2, except that the 0.92 mg / mL NdCl3·6H2O solution in step (c) was replaced with a 1.84 mg / mL NdCl3·6H2O solution.
[0061] Example 7, rare earth metal Nd single atom doped Ru-based catalyst (Ru 0.5 Nd 0.05 Preparation of -NMC:
[0062] The sample was prepared in the same manner as in Example 2, except that the amount of RuCl3 solution added in step (c) was changed from 1 mL to 0.5 mL.
[0063] Example 8, rare earth metal Nd single atom doped Ru-based catalyst (Ru 1.5 Nd 0.05 Preparation of -NMC:
[0064] The sample was prepared in the same manner as in Example 2, except that the amount of RuCl3 solution added in step (c) was changed from 1 mL to 1.5 mL.
[0065] Example 9: Rare earth metal Ce single atom doped Ru-based catalyst (Ru1Ce 0.05 Preparation of -NMC:
[0066] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added dropwise in step (c) was replaced with a 0.96 mg / mL CeCl3·7H2O solution from a 0.92 mg / mL NdCl3·6H2O solution.
[0067] Example 10, Rare earth metal La single atom doped Ru-based catalyst (Ru1La 0.05 Preparation of -NMC:
[0068] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added dropwise in step (c) was replaced with a 0.95 mg / mL LaCl3·7H2O solution from a 0.92 mg / mL NdCl3·6H2O solution.
[0069] Example 11: Rare earth metal Sm single atom doped Ru-based catalyst (Ru1Sm 0.05 Preparation of -NMC:
[0070] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added in step (c) was replaced by a 1.14 mg / mL Sm(NO3)3·6H2O solution from a 0.92 mg / mL NdCl3·6H2O solution.
[0071] Example 12: Rare earth metal Gd single atom doped Ru-based catalyst (Ru1Gd 0.05 Preparation of -NMC:
[0072] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added in step (c) was replaced from 0.92 mg / mL NdCl3·6H2O solution to 1.16 mg / mL Gd(NO3)3·6H2O solution.
[0073] Example 13, rare earth metal Er single atom doped Ru-based catalyst (Ru1Er 0.05 Preparation of -NMC:
[0074] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added in step (c) was replaced from 0.92 mg / mL NdCl3·6H2O solution to 1.18 mg / mL Er(NO3)3·6H2O solution.
[0075] Example 14: Rare earth metal Dy single atom doped Ru-based catalyst (Ru1Dy 0.05 Preparation of -NMC:
[0076] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added in step (c) was replaced from 0.92 mg / mL NdCl3·6H2O solution to 1.17 mg / mL Dy(NO3)3·6H2O solution.
[0077] Example 15, rare earth metal Y single atom doped Ru-based catalyst (Ru1Y 0.05 Preparation of -NMC:
[0078] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added in step (c) was replaced by a 0.98 mg / mL Y(NO3)3·6H2O solution from a 0.92 mg / mL NdCl3·6H2O solution.
[0079] Example 16, rare earth metal Pr single atom doped Ru-based catalyst (Ru1Pr 0.05 Preparation of -NMC:
[0080] The sample was prepared by the same method as in Example 2, except that the rare earth metal salt solution added in step (c) was replaced from 0.92 mg / mL NdCl3·6H2O solution to 1.12 mg / mL Pr(NO3)3·6H2O solution.
[0081] Application Example 1
[0082] The performance of the nitrogen-doped mesoporous carbon-supported Ru-based catalyst (Ru1-NMC) prepared in Example 1 was tested for the hydrogen evolution reaction in electrolysis of water.
[0083] In 1M KOH electrolyte, the catalyst was tested for electrochemical hydrogen evolution reaction in a three-electrode system using Shanghai Chenhua CHI-660E electrochemical workstation, where the carbon cloth coated with the catalyst was used as the working electrode, the Hg / HgO electrode was used as the reference electrode, and the carbon rod was used as the counter electrode.
[0084] The specific operation is as follows: the catalyst is placed in an Ar-saturated 1M KOH electrolyte, and the polarization curve is set to scan from a low potential of -0.8V to a high potential of -1.5V at a scan rate of 5mV / s, and the cathode hydrogen evolution reaction test is performed. The activity parameters characterizing its hydrogen evolution reaction performance are the overpotential required for a certain current density, mass activity, etc. ( Figure 5 , Figure 6 ).
[0085] Application Example 2
[0086] The rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.05 -NMC) was used to test the performance of hydrogen evolution reaction by electrolysis of water.
[0087] In 1M KOH electrolyte, the catalyst was tested for electrochemical hydrogen evolution reaction in a three-electrode system using Shanghai Chenhua CHI-660E electrochemical workstation, where the carbon cloth coated with the catalyst was used as the working electrode, the Hg / HgO electrode was used as the reference electrode, and the carbon rod was used as the counter electrode.
[0088] The specific operation is as follows: the catalyst is placed in an Ar-saturated 1M KOH electrolyte, and the polarization curve is set to scan from a low potential of -0.8V to a high potential of -1.5V at a scan rate of 5mV / s, and the cathode hydrogen evolution reaction test is performed. The activity parameters characterizing its hydrogen evolution reaction performance are the overpotential required for a certain current density, mass activity, etc. ( Figure 5 , Figure 6 ).
[0089] Figure 5 The linear sweep voltammetry (LSV) curves of the electrocatalytic hydrogen evolution performance of different catalysts in an alkaline environment (1M KOH) are shown in the figure. 0.05 -NMC catalyst reaches 10 mA cm -2 The overpotential required for the current density is only 12 mV, which is comparable to that of commercial Pt / C catalysts (η 10 =25mV). At the same time, the catalyst -2 The overpotential required for the Ru1-NMC catalyst to reach 10 mA cm -2 The overpotential required for the current density is 26 mV.
[0090] Figure 6 The mass activity of different catalysts is calculated at -0.15V vs. RHE. By comparison, it can be seen that Ru1Nd 0.05 The mass activity of the -NMC catalyst is 10.5 times that of the commercial Pt / C catalyst, showing excellent intrinsic activity.
[0091] Application Example 3
[0092] The rare earth metal Nd single atom doped Ru-based catalyst (Ru1Nd 0.05 -NMC) as cathode and commercial NiFe foam catalyst as anode to make a membrane electrode, in which the precious metal loading is 100 μg Ru / cm 2 , assembled it with end plates into an anion exchange membrane electrolyzer, and carried out water electrolysis test in 1M KOH electrolyte.
[0093] Figure 7 This is the LSV curve of the rare earth metal Nd single atom doped Ru-based catalyst used in the cathode of the AEM electrolyzer at different temperatures (1M KOH). As the temperature increases, its water electrolysis performance gradually increases. Foam NiFe||Ru1Nd 0.05 -NMC reaches 1A cm at 80℃ -2 The overpotential required for the current density is 1.88V (80℃).
[0094] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the invention shall be defined by the attached claims and their equivalents.
Claims
1. A rare earth element doped Ru-based catalyst, characterized in that: The molecular formula is Ru x RE y -NMC, Ru metal ions and rare earth metal ions are loaded on nitrogen-doped mesoporous polymers; wherein x=0.5-3, y=0.01-0.1, and RE is any one of neodymium, cerium, lanthanum, samarium, gadolinium, erbium, dysprosium, yttrium, and praseodymium.
2. A method for preparing a rare earth element doped Ru-based catalyst, characterized in that: The steps include: (1) Place the template F127 in a beaker, add deionized water, fully dissolve it, then add methyltetramine, and stir evenly to prepare solution A; At the same time, add deionized water to another beaker, then add the phenolic compound, and stir thoroughly to prepare solution B; Then, solution A and solution B are mixed and stirred evenly, and then placed in a polytetrafluoroethylene reactor for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled to room temperature in an oven. The reaction product is centrifuged several times with deionized water and then freeze-dried to obtain a nitrogen-doped mesoporous polymer NMP. (2) dissolving the nitrogen-doped mesoporous polymer NMP in deionized water, ultrasonicating and stirring to obtain a solution C; Subsequently, the ruthenium trichloride aqueous solution and the rare earth metal salt solution were added dropwise to the solution C to obtain a mixed solution D, which was stirred until uniform and then freeze-dried to obtain a nitrogen-doped mesoporous polymer loaded with metal precursor Ru x RE y -NMP; (3) x RE y -NMP was fully ground, and then carbonized at 600-900°C in an Ar atmosphere, kept warm, and then naturally cooled to room temperature to obtain a rare earth element-doped Ru-based catalyst Ru x RE y -NMC.
3. The method for preparing a rare earth element-doped Ru-based catalyst according to claim 2, characterized in that: In the step (1), methyltetramine is added in 4 to 6 portions; the phenolic compound is a mixture of one or more of 2-aminophenol, 3-aminophenol and 4-aminophenol; The mass ratio of template F127 to phenolic compound is 0.3-0.7:1; The mass ratio of the phenolic compound to the total amount of methyltetramine added to solution A is 1-2:
1.
4. The method for preparing a rare earth element-doped Ru-based catalyst according to claim 2, characterized in that: In the step (1), the hydrothermal reaction conditions are: heating to 80-100°C at a heating rate of 2°C / min, and then keeping warm for 20-24 hours; the freeze-drying conditions are -40--60°C, and the vacuum degree is 5-20 kPa.
5. The method for preparing a rare earth element-doped Ru-based catalyst according to claim 2, characterized in that: In the step (2), after being dissolved in deionized water, the concentration range of the nitrogen-doped mesoporous polymer NMP aqueous solution is 2 to 7 mg / mL; the rare earth metal salt solution is any one of a neodymium trichloride hexahydrate aqueous solution, a cerium trichloride heptahydrate aqueous solution, a lanthanum trichloride heptahydrate aqueous solution, a samarium nitrate hexahydrate aqueous solution, a gadolinium nitrate hexahydrate aqueous solution, an erbium nitrate hexahydrate aqueous solution, a dysprosium nitrate hexahydrate aqueous solution, a yttrium nitrate hexahydrate aqueous solution, and a praseodymium nitrate hexahydrate aqueous solution.
6. The method for preparing a rare earth element-doped Ru-based catalyst according to claim 2, characterized in that: In the step (3), in the prepared catalyst, the loading amount of Ru is 0.5-10 wt %, and the loading amount of RE is 0.01-0.4 wt %.
7. The method for preparing a rare earth element-doped Ru-based catalyst according to claim 2, characterized in that: In the step (3), in the prepared catalyst, the metal Ru exists in the form of nanoparticles and single atoms with an average diameter in the range of 3 to 6 nm, and the rare earth metal exists only in the form of single atoms, forming a structure of Ru nanoparticles and Ru and RE double single atoms.
8. Application of a rare earth element doped Ru-based catalyst as cathode in AEM electrolyzer for hydrogen production by water electrolysis.
9. The use according to claim 8, characterized in that: The catalyst is dispersed in a Nafion mixed solution to obtain a catalyst dispersion, which is then evenly drop-coated on the electrode surface.
10. The use according to claim 9, characterized in that: The Nafion mixed solution comprises water, isopropanol and Nafion, and the volume ratio of the three is 4:1:0.1-0.2; the catalyst concentration in the dispersion is 10-15 mg / mL.
Citation Information
Cited By
Rare earth electrolyte solution activity coefficient prediction method based on machine learning
CN120452565A
Ru-RE2O3 catalyst as well as preparation method and application thereof
CN122257033A
